“Quella importanza di materia”: Women and saints in Francesco Pona’s Galeria delle Donne Celebri - Kubas, Magdalena Maria (Quaderni d'Italianistica)

(untitled) (Iter Press, 2021)
In his Galeria delle Donne Celebri, a collection of twelve short stories about famous female figures, Francesco Pona “depicts” four lascivious women and four chaste women from classical antiquity, and four saints from the early and medieval Christian era. Pona, a writer and medical doctor, rationally studied the Other, that is, women; his narrator in Galeria analyzes the characters’ bodies and behaviours, but almost never their psychology. In this essay, I examine the “portraits” of saints in Pona’s Galeria (Magdalene, Barbara, Monica, and Elisabeth of Hungary) and the observation of otherness by a collector who studied both the natural and miraculous aspects of female sanctity. As interest in the ancient and medieval saints was typical of the period following the Council of Trent, I investigate Pona’s short stories within the framework of the decree on saints and relics issued in 1563. I also consider the misogynistic controversy that took place in Italy between the sixteenth and seventeenth centuries, as well as Pona’s treatise Della Eccellenza et Perfettione ammirabile della Donna.